2015
DOI: 10.1111/bjdp.12081
|View full text |Cite
|
Sign up to set email alerts
|

Young Chinese children's beliefs about the implications of subtypes of social withdrawal: A first look at social avoidance

Abstract: The goal of this study was to examine young Chinese children's beliefs about the implications of different subtypes of social withdrawal (e.g., shyness, unsociability), including for the first time, social avoidance. Participants were 133 children in kindergarten (n = 58, Mage  = 70.85 months) and grade 1 (n = 75, Mage  = 83.49 months). Children were presented with vignettes describing hypothetical peers displaying shy, unsociable, avoidant, and socially competent behaviours and were then asked a series of que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

10
72
3
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(94 citation statements)
references
References 64 publications
10
72
3
9
Order By: Relevance
“…However, we could question whether this subtype would have been identified as a subtype of a socially withdrawn child. This is a very different methodology to that used by Ding et al (2015), but clearly demonstrated how in Turkey a novel subtype of social withdrawal existed (regulated withdrawal), which fits with their cultural values and norms. € Ozdemir et al used openended questions to assess children's understanding of social withdrawal behaviour and to define categories of behaviour.…”
mentioning
confidence: 97%
See 4 more Smart Citations
“…However, we could question whether this subtype would have been identified as a subtype of a socially withdrawn child. This is a very different methodology to that used by Ding et al (2015), but clearly demonstrated how in Turkey a novel subtype of social withdrawal existed (regulated withdrawal), which fits with their cultural values and norms. € Ozdemir et al used openended questions to assess children's understanding of social withdrawal behaviour and to define categories of behaviour.…”
mentioning
confidence: 97%
“…Ding et al (2015) have explored young Chinese children's understanding of three subtypes of social withdrawal and the children's beliefs about the implications of being a socially withdrawn child within each subtype. Ding et al (2015) have explored young Chinese children's understanding of three subtypes of social withdrawal and the children's beliefs about the implications of being a socially withdrawn child within each subtype.…”
mentioning
confidence: 99%
See 3 more Smart Citations